Comparative Analysis of C-repeat Binding Factors (CBFs) in Tomato and Arabidopsis - Heidari,Parviz (2019)
Abstract Cold stress is one of the limiting factors of plant production that plants use different mechanisms for cold tolerance. CBF genes play critical role to regulate the cold responsive genes. To better understand of CBF gene functions, the tomato-CBFs and Arabidopsis-CBFs were evaluated using bioinformatics tools, and finally the expression patterns of SlCBF1 gene were analyzed under 10 and 4˚C in two contrasting tomato species (Solanum lycopersicum and S. habrochaites). The different cis regulatory elements were observed in promoter region of SlCBF1 and AtCBF1 genes, and ICE1, COR and HOS1 proteins exhibited high interaction with CBFs. The results of Real time PCR of SlCBF1 exhibited that under 10 and 4 ˚C, SlCBF1 was down regulated in cold sensitive tomato genotype while it was slightly up-regulated in cold tolerant genotype at 4 ˚C. The results showed that the SlCBF1 and AtCBF1 genes have differential expression in cold stress.